Hydrogeophysical Characterization of Volcanic Aquifers Using Integrated Resistivity and Induced Polarization in Mount Tumpa, Manado - As'ari As'ari; Seni Herlina J. Tongkukut; Mahendra Kusuma Nugraha (Jurnal Ilmiah Sains, 2026)
This study investigates the aquifer system in the Mount Tumpa area, North Sulawesi, Indonesia, using integrated electrical resistivity and induced polarization (IP) methods. Data were acquired with a dipole–dipole array, enabling high lateral resolution of subsurface heterogeneity. Resistivity inversion was used to delineate aquifer geometry, while IP data were analyzed to identify zones of enhanced electrochemical polarization related to lithological and mineralogical variations. Aquifer zones are characterized by low resistivity values (< 9.17 Ωm). On Line 1, an aquifer is identified at 100–130 m and depths of 15–25 m; on Line 2, at 215–230 m and depths of 10–20 m. On Line 3, three distinct aquifer units are resolved: (1) 150–175 m at depths ≥ 75 m, (2) 220–235 m at 30–40 m, and (3) 285–305 m at 35–45 m. These findings indicate a multi-layered groundwater system with variable depth distribution. Chargeability responses are high on Lines 1 and 3 and moderate on Line 2, suggesting the presence of polarizable materials such as volcanic clay, iron oxides, and organic-rich layers. These materials may influence groundwater geochemical behavior through adsorption and redox processes; however, IP responses do not directly indicate groundwater quality in the absence of hydrochemical data. The subsurface is interpreted as a layered volcanic aquifer system, where groundwater is primarily hosted in permeable lapilli and volcanic ash deposits overlying compact lava, with additional storage in fractured lava zones. The identified aquifers are interpreted as shallow to intermediate systems based on geophysical evidence, although further hydrogeological validation is required. Keywords: resistivity method; induced polarization; chargeability; Mount Tumpa; aquifer characterization